Field efficacy study with a new 3 strains escherichia coli bacterin again neonatal piglets diarrhoea - ΚΥΡΙΑΚΗΣ, ΣΠ. Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Piglets from sows vaccinated with 3 E. coli pilus antigens (09:K35, 99/0157:K88ac and 020, K101:987P) were shown to be protected against natural neonatal diarrhoea. Mortality was less (P<0,005) in the group of piglets from vaccinated sows, up to the age of 35 days, as compared to controls. Also the reduction in scours and the general health status was better in the same group of piglets. The average live weight gain was improved in the group of piglets from vaccinated sows over a 3 week period (weaning age) and at 35 days (P<0,005). This field efficacy study was carried out in a commercial swine operation with 1.200 sows under production (22.500 piglets/year) and with the involvement of 1546 piglets.